Review of Asprosin as new Biomarker for diagnosis different Diseases - Atta, Safaa Ehssan; Baydaa Ahmed Abed,; Isam Noori Salman,; Lujain A. Ghannawi, (University of Thi-Qar Journal of Science, 2023)
This study was designed to investigate the connections between (Inflammation, Cardiovascular diseases (CVDs),-diabetes mellitus,-Obesity,-polycystic ovary syndrome, thyroid and cancer )-and asprosin hormone. Asprosin is present in high amounts in a variety of diseases that are considerably manifested in several cases and illnesses Asprosin hormone is newly adipokine helps the liver produce glucose. White adipose tissue secretes the novel hormone asprosin, which stimulates the release of hepatic glucose, making protein a possible target for new treatments for obesity and  type 2 diabetes mellitus. Exons (65 and 66) of the gene( Fibrillin 1 (FBN1)), which was recently shown to be a new hormone released by white adipose tissues, are the final two exons that code for asprosin. However, further research is needed to fully understand how asprosin affects pancreatic beta-cells, leading to pathologically elevated cellular dysfunction and inflammation. Asprosin hormone is raised  in human  with metabolic disease. The findings imply that asprosin hormone  may be crucial for maintaining insulin and glucose homeostasis as well as acting as a risk factor for a number of diseases, including CVDs, obesity,  T2DM, cancer, hypothyroidism, and PCOS. Depleting asprosin or attenuating its activity may potentially offer a novel therapeutic option for the treatment of T2DM and obesity.